PERSONNEL WORK LIFE QUALITY AND ENGAGEMENT: EXAMPLE OF A NORDIC BUSINESS INFORMATION TECHNOLOGY COMPANY - Blumberga, Solveiga; Akmene, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Work life quality and engagement have been widely studied and terms are being used in the context of working life. Together these terms have not been studied much. Although the connection between these two has been proven as significant in various researches. The aim of every company is to perform well and make a profit, or just one of these aims depending on the type of enterprise and their business. The aim of the research is to determine personnel work life quality and work engagement, their differences, and interconnection in a Nordic business information technology company’s division in Latvia and Finland. Three research questions were set: What is the evaluation of personnel work life quality and work engagement; Is there a statistically significant connection between personnel work life quality and work engagement; Are there statistically significant differences in results of work life quality and work engagement in a Nordic business information technology company’s divisions in Latvia and Finland. The following methods were used for data acquisition: work life quality questionnaire; Work engagement questionnaire. Analysis of the results showed that the evaluation of work life quality and work engagement is medium-high. There is a statistically significant correlation between work life quality and work engagement. Statistically significant differences were found between personnel work life quality and work engagement in both countries. Various work life quality factors promote work engagement. For both divisions, the most challenging is balancing work and private life of the employees. Employees in Finland would evaluate the company’s inner communication higher if they felt more engaged in decision making. Researches of differences reveal that employees of Latvian companies show higher results in social integration and employer and company evaluation than personnel in Finland.